(untitled) (PerCursos, 2024)
This article discusses the centrality of the the discourse of ethical-moral training in building consensus around the National Program of Civic-Military Schools. To do this, it analyzes the two main documents that guide the implementation of the program and indicate the principles it defends: the Manual of Civic-Military Schools and the Guidelines of Civic-Military Schools. The analysis is carried out in the light of the Gramscian categories of consensus, collective will, ethical-moral formation and hegemony. The results show that the documents emphasize the importance of reviving civic values that have supposedly lost their centrality in the education of students. They therefore advocate the formation of good behavior and attitudes, seeking to build a new formative rationality in schools.